History for the Anthropocene - Robin, Libby (History compass, 2007)
Global history has become the business of more than just historians. This paper explores the history of scientific historiography, particularly a recent initiative of the Global Change community to write an Integrated History and future Of People on Earth (IHOPE). A new geological epoch, the Anthropocene, has been declared, reflecting the scientific fact that anthropogenic change is now shaping planetary systems. Describing changes to the Earth system over time demands understanding of the history of the biophysical factors, the human factors and their integration. While global warming has motivated the recent initiative to write global history, the global atomic era also provided an incentive for scientists to write global history, as was revealed in the 1940s UNESCO initiatives for a Scientific and Cultural History of Mankind and an International Union for the History of Science. We review recent developments in world and environmental historiography, and popular ‘millennial’ projects, such as the Clock of the Long Now, to identify potential common interests between historians and non-historians writing world history at very different scales, and for different audiences.